How sponsors should bring relevant-added value to esports - Freitas, Bruno Duarte Abreu (2022)
This paper aimed to determine what types of relevant-added value esports fans most want sponsors to bring to them and to the competitive gaming industry. A review of the literature permitted the development of a conceptual model which was subsequently improved by analysing empirical data. A quantitative exploratory research was conducted on 1,359 esports fans who were sampled through a non-probability purposive heterogeneous method. Data was collected through a closed-ended online structured survey. The data showed that two of the three most wanted means for bringing relevant added value are by directly helping the esports industry rather than focusing on the fans. Specifically, supporting the tournaments and pro-players and promoting good practice and integrity were highly valued. Most brands are still unaware of how to conduct effective esports sponsorships. By being one of the first studies in this area, this research provides brands with useful guidelines for developing sustainable esports sponsorships.